Association between serum paraoxonase and plasma nitric oxide in pre-eclampsia - Suneja, Shilpa; Saxena, Rahul; Saxena, Raj; Sharma, Dilutpal; Lal, Alok Milton (International Journal of Advances in Medicine, 2017)
Background: It is well accepted that oxidative stress plays a crucial role in the development of endothelial dysfunction leading to Pregnancy Induced Hypertension (PIH). However, studies related to altered levels of paraoxonase and nitric oxide in PIH subjects are still in obscure. In this context, the present study was undertaken to assess serum Paraoxonase (PON), Nitric Oxide (NO) levels along with other markers of oxidative stress i.e. erythrocyte Malondialdehyde (MDA), plasma ascorbic acid levels in the blood samples of PIH subjects and to determine their relation in etio-pathogenesis of PIH complication. Methods: Markers of oxidative stress (PON, MDA, and ascorbic acid) and endothelial dysfunction (serum NO) were estimated in 20 normotensive pregnant women (Group I) and 20 PIH women (Group II) by using standard methods. Data obtained from both the groups were statistically compared with age matched 20 healthy non pregnant women (Control group) by using student’s t-test. Results: Serum PON and erythrocyte MDA levels were increased significantly whereas marked depletion in plasma NO and vitamin C levels (P <0.05, P <0.001) were observed in PIH subjects. In addition, PON levels were inversely correlated with endothelial dysfunction. However, only plasma NO levels were decreased significantly in group I subjects whereas other parameters were altered insignificantly (P <0.1) in group I subjects. Conclusion: These findings reflects the importance of antioxidant rich diet in the prevention of PIH complication and emphasizes the early assessment of serum paraoxonase and NO levels as efficient diagnostic marker to predict future risk of PIH development.